Effect of lockdown during COVID-19 on migraine: A longitudinal cohort study - Verhagen, Iris E; van Casteren, Daphne S; de Vries Lentsch, Simone; Terwindt, Gisela M (Cephalalgia, 2021)
The objective of this study was to assess whether migraine-related outcomes changed during intelligent lockdown when compared with the prior period. This was a cohort study evaluating the first month of intelligent lockdown in the Netherlands (12 March to 8 April 2020) compared with one baseline month (13 February to 11 March 2020). We identified 870 migraine patients treated at the Leiden Headache Center with headache e-diaries during the period of interest. Adherence to the e-diary had to be ≥80%, yielding 592 enrolled patients. Intelligent lockdown led to a decrease in monthly migraine days (-0.48; 95% CI: -0.78 to -0.18, = 0.002) and acute medication days (-0.48; 95% CI: -0.76 to -0.20, < 0.001), and an increase in general well-being (0.11; 95% CI: 0.06 to 0.17, < 0.001). No differences in non-migrainous headache days and pain coping were observed. Consistent results were found in a subset that was followed for 4 months. Our findings imply that intelligent lockdown measures can improve migraine disability despite of the potential negative effects of COVID-19 and lockdown. We hypothesise that this effect is a combined result of working from home, scaling down demanding social lives, and freedom to choose how to organise one's time.